EXAMINING INTERNAL QUALITY SYSTEM FOR STUDY PROGRAM ACCREDITATION IN HIGHER EDUCATION - Sauri , R. Supyan; Ramlan, (International Journal of Psychosocial Rehabilitation, 2020)
This research aimed to describe the improvement of study program’s performance in higher education by implementing Internal Quality Assurance System (SPMI) as an effort to improve the quality of educational input, processes, and output. This step was considered crucial since problems of study program’s performance were extremely complex, starting from input, teaching and learning processes, to the fulfillment of higher education quality standards. Other problems in improving study program’s performance were the less- optimal implementation of higher education quality standards, both academically and non-academically. This research used a qualitative approach with a case study method. The research was conducted at Nusantara Islamic University, Bandung, Indonesia. Data collection techniques used: direct observation, searching documents and archives, and in-depth interviews. The results indicated that there were Internal Quality Assurance System (SPMI) policies and concepts in the form of academic quality standard documents and non-academic quality standard documents prepared by the Directorate of Quality Assurance (DPM) as a reference in formulating quality standards at Study Program level. The Directorate of Quality Assurance (DPM) coordinated with the Quality Assurance Cluster (GPM) and the Quality Assurance Unit (UPM) in determining, implementing, evaluating, controlling and improving the quality standards of study programs. In addition, the Internal Quality Assurance System was implemented by arranging a draft in the form of Internal Assurance System cycle. Further, obstacles in conducting this cycle were the low commitment of the leaders and the limited number of auditors. Steps for anticipating these obstacles were providing experts in the implementation of Internal Quality Assurance System, conducting training for young auditors, growing the spirit of quality assurance, and carrying out evaluation every semester.